Arabisms as a stable part of the lexicon of the Belarusian Tatars (by the example of Ibragim Hosenevich’s kitab) - Mirieva, Nailya (Journal of the Belarusian State University. Philology, 2022)
The subject of the research is the functioning of the Arabic vocabulary in the monuments of the Belarusian Tatars. Ibragim Hosenevich’s kitab was chosen as the material for the analysis. The following methods are used in the work: vocabulary classification, which determines the systemic relations between words, and an analysis of lexicogrammar. This classification is necessary to present a complete picture of the functioning of the Arabic vocabulary in the Slavic text. The study provides examples with translation and indication of the phonetic, graphical and word-formation features of Arabisms, as well as a comparative analysis of quotations from the Koran and I. Hosenevich’s kitab. Separate lexical units are accompanied by grammatical commentary and dictionary form and are considered in context with indication of grammatical indicators. The scientific novelty of the work lies in the study of Arabisms of the original monument of the Belarusian Tatars, the eastern vocabulary of which was not previously considered. The relevance of this topic is due to the intensive development of kitabistic study, and the results of the work carried out can be used to describe lexical units in the composition of summary dictionaries. The lexical analysis of each monument makes it possible to determine the continuity of linguistic patterns for further cultural and historical research.
Keywords: arabisms; kitabistics; Belarusian Tatar’s manuscripts